Remote Relaxation and Acceptance Training for the Management of Stress in Cancer Patients: A Study Protocol - Marzorati, Chiara; Pizzoli, Silvia Francesca Maria; Grasso, Roberto; Pravettoni, Gabriella (Frontiers in Psychology, 2021)
Background: Cancer patients are now facing a double distinctive challenge of survival against both the disease and fear of contracting COVID-19. This challenge has resulted in the forced adoption of social distancing measures and reorganization of the delivery of medical and psychological treatments. The perceived loneliness and uncertainty increased distress and symptoms burden. In the current period, eHealth interventions might provide valuable benefits in the field of cancer care. Objective: The overall goal of the study protocol will be to provide an innovative intervention for cancer patients based on an online platform, to help them manage and prevent psychological problems related to social isolation. Specifically, the efficacy of two web-based interventions aimed at lowering stress in cancer patients will be tested and compared. Methods: One hundred and fifty participants (75 per group) will be enrolled in a two-group randomized trial. The two interventions will be composed either by exercises on relaxation and meditation practices, presented in both automated online content and interactive group sessions or by fixed psychoeducational online content. Stress, anxiety, and depressive symptoms, distress, resilience, and perceived social isolation will be measured before the start of the interventions (T0), 2 weeks (T1), 4 weeks (T2), and 2 months (T3) after the beginning of the interventions in both groups. A repeated measures ANOVA will be performed to test differences in the questionnaires' scores between groups across the four-time points. Expected Results: We hypothesized greater improvement in the specific domain of stress symptoms (IES-R) assessed in the group receiving the interactive intervention, compared to the group which will receive only fully automated psychoeducational content. Secondarily, we expect the same trend of improvement across all the psychological variables in the blended intervention group. Conclusions: Implementing these practices on people who are forced into mandatory social isolation may help them become more aware of their mind-body condition and reduce negative effects. Moreover, relaxation techniques help individuals in achieving a greater state of well-being, increasing the ability to cope with stressful situations (resilience), and strengthening the immune system.